1991
DOI: 10.1159/000174774
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological Study in Patients with Coronary Artery Disease

Abstract: Hemorheological parameters (viscosity of whole blood, plasma viscosity, hematocrit, velocity of red blood cells) were studied in 30 patients with coronary artery disease (15 patients with acute myocardial infarction, 15 patients with chronic angina), 14 subjects at high risk for ischemic heart disease and 14 normal volunteers matched for sex and age. Viscosity of whole blood was high in all coronary disease patients and in high-risk subjects as compared with controls. Velocity of red blood cells was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 28 30 Mares et al evaluated the role of the blood viscosity in patients with ischemic heart disease and found that high viscosity is an independent predictor of both in-hospital and long-term adverse outcomes. 31 Blood viscosity is also a risk factor in cardiovascular events. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 28 30 Mares et al evaluated the role of the blood viscosity in patients with ischemic heart disease and found that high viscosity is an independent predictor of both in-hospital and long-term adverse outcomes. 31 Blood viscosity is also a risk factor in cardiovascular events. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of deformation and stress of cell is of great importance by various physiological and pathological parameters, such as temperature, morphology, osmotic pressure, ATP effect, parasite invasion, genetic diseases (e.g., sickle cell anaemia). 16 Erythrocyte deformability also becomes altered in other diseases such as diabetes mellitus, 17-21 essential hypertension, [22][23][24][25][26] arteriosclerosis, coronary artery disease 27,28 and cancer. 29 The shear modulus in this study can be employed to nd the shape of a spherical particle submerged in a horizontal ow of a liquid.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable epidemiological evidence indicating that there is a higher incidence of myocardial infarctions, strokes, and sudden cardiac death in man in the morning (Marshall 1977, Muller et al 1985, 1987. There is also evidence of higher viscosity in patients with high blood pressure, coronary heart disease and stroke (Parfenov & Belousov 1989, Leschke et al 1990, Koenig et al 1991, Mares et al 1991. It has also M .…”
Section: Discussionmentioning
confidence: 99%